2018
DOI: 10.1016/j.jtho.2017.10.031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Plasma Epstein-Barr Virus DNA in Pulmonary Lymphoepithelioma-like Carcinoma (LELC) Patients

Abstract: High baseline EBV DNA concentration is an independent poor prognostic marker in patients with pulmonary LELC. These results should be confirmed in larger prospective trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 33 publications
2
45
0
1
Order By: Relevance
“…ALK alteration was detected positive in three PLELC patients in our study, while only one was reported in the literature by Ose et al 38 The variant rates may be due to the small sample size of each study which warrants further investigation. In the study by Gou and Wu which demonstrated the frequencies of driver mutations in nonsmall cell lung cancer in China, 19 the mutation rates of EGFR were 48.4% (675/1795), 4.3% (9/208), and 28.2% (570/2021) in lung adenocarcinoma, squamous cell cancer 36 Hong Kong, China 11 NA 0 NA NA Liang et al 8 Guangzhou, China 52 0/11 NA NA NA Liu et al 29 Guangzhou, China 32 0 NA NA NA Wang et al 28 Guangzhou, China 42 1 0 NA NA Fang et al 37 Guangzhou, China 113 2 0 NA NA Chang et al 30 Tai Wan, China 66 8 0 0 0 (BRAF) Ose et al 38 Osaka, Japan 1 0 1 NA NA Hong et al 31 Guangzhou, China 91 0 0 NA 14 (P53) Lin et al 39 Guangzhou, China 39 0/19 NA NA NA Lin et al 40 Fuzhou, China 20 0/3 0/2 0/1 NA Xie et al 10 Guangzhou, China 429 2 0 0 NA Zhou et al 41 Guangzhou, China 27 0 0 1 7 (P53) Yin et al 42 Guangzhou 43 An et al reported that the mutation rate of driver genes might differ among different histology subtypes and smoking status. 44 EGFR and ALK alteration is rare in PLELC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALK alteration was detected positive in three PLELC patients in our study, while only one was reported in the literature by Ose et al 38 The variant rates may be due to the small sample size of each study which warrants further investigation. In the study by Gou and Wu which demonstrated the frequencies of driver mutations in nonsmall cell lung cancer in China, 19 the mutation rates of EGFR were 48.4% (675/1795), 4.3% (9/208), and 28.2% (570/2021) in lung adenocarcinoma, squamous cell cancer 36 Hong Kong, China 11 NA 0 NA NA Liang et al 8 Guangzhou, China 52 0/11 NA NA NA Liu et al 29 Guangzhou, China 32 0 NA NA NA Wang et al 28 Guangzhou, China 42 1 0 NA NA Fang et al 37 Guangzhou, China 113 2 0 NA NA Chang et al 30 Tai Wan, China 66 8 0 0 0 (BRAF) Ose et al 38 Osaka, Japan 1 0 1 NA NA Hong et al 31 Guangzhou, China 91 0 0 NA 14 (P53) Lin et al 39 Guangzhou, China 39 0/19 NA NA NA Lin et al 40 Fuzhou, China 20 0/3 0/2 0/1 NA Xie et al 10 Guangzhou, China 429 2 0 0 NA Zhou et al 41 Guangzhou, China 27 0 0 1 7 (P53) Yin et al 42 Guangzhou 43 An et al reported that the mutation rate of driver genes might differ among different histology subtypes and smoking status. 44 EGFR and ALK alteration is rare in PLELC.…”
Section: Discussionmentioning
confidence: 99%
“…1,6,7 Since then, around 1200 cases have been reported in the literature, mostly from Asian countries. [8][9][10] Due to the rarity of this tumor, the standard treatment strategy for advanced PLELC patients remains controversial and a multidisciplinary management has been recommended. 1,8,11,12 Epidermal growth factor receptor (EGFR) and anaplastic lymphoma kinase (ALK) are reported to play an important role in the pathogenesis of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary lymphoepithelioma-like carcinoma (LELC) is a rare subtype of non-small cell lung cancer (NSCLC), accounting for < 1% of all histologic type of lung cancers. So far only ∼600 cases have been reported in the English-language literature (1)(2)(3)(4)(5)(6)(7). Histologically, the disease is characterized by epithelial tumor cells nests surrounded or infiltrated by numerous lymphocytes (1) ( Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other lung carcinomas often showed signals of neither EBERs, nor latent membrane protein 1 or viral capsid antigen (9). Plasma EBV-deoxyribonucleic acid (DNA) is usually positive in patients with pulmonary LELC (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation